2010
DOI: 10.1038/mp.2010.109
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of major depressive disorder: new results, meta-analysis, and lessons learned

Abstract: Major depressive disorder (MDD) is a common complex disorder with a partly genetic etiology. We conducted a genome-wide association study of the MDD2000+ sample (2431 cases, 3673 screened controls and >1 M imputed single-nucleotide polymorphisms (SNPs)). No SNPs achieved genome-wide significance either in the MDD2000+ study, or in meta-analysis with two other studies totaling 5763 cases and 6901 controls. These results imply that common variants of intermediate or large effect do not have main effects in the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
335
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(349 citation statements)
references
References 55 publications
(71 reference statements)
9
335
1
4
Order By: Relevance
“…Heritability rates for depression are estimated between 40% and 50%, suggesting a substantive genetic contribution to risk for depression (Lohoff, 2010). Further, specific candidate genes have been investigated, including the serotonin transporter gene (Caspi, Hariri, Holmes, Uher, & Moffitt, 2010), the Brain-Derived Neurotrophic Factor (BDNF) gene (Hashimoto, 2010) and the Tryptophan Hydroxylase gene (Zill, Baghai & Ackenheil, 2004; for review see, Wray et al, 2012). Diathesis-stress theories develop the gene x environment model suggesting that stress interacts with a potential predisposition leading to psychopathology (Monroe & Reid, 2009;Monroe & Simons, 1991).…”
Section: Example 4: Individual Differences In Contingency Learning Anmentioning
confidence: 99%
“…Heritability rates for depression are estimated between 40% and 50%, suggesting a substantive genetic contribution to risk for depression (Lohoff, 2010). Further, specific candidate genes have been investigated, including the serotonin transporter gene (Caspi, Hariri, Holmes, Uher, & Moffitt, 2010), the Brain-Derived Neurotrophic Factor (BDNF) gene (Hashimoto, 2010) and the Tryptophan Hydroxylase gene (Zill, Baghai & Ackenheil, 2004; for review see, Wray et al, 2012). Diathesis-stress theories develop the gene x environment model suggesting that stress interacts with a potential predisposition leading to psychopathology (Monroe & Reid, 2009;Monroe & Simons, 1991).…”
Section: Example 4: Individual Differences In Contingency Learning Anmentioning
confidence: 99%
“…Nominally significant associations will include many false-positives. Nevertheless it is noteworthy that SNPs in the gene for galanin (GAL) were among the top 10 genes whose variation was associated with MDD in a recent GWAS (55). One way to improve sensitivity is to take a system-based approach: if galanin is mechanistically involved in depression, genetic variation in the peptide and its receptors should exert similar influences, despite the fact the genes are located on entirely different chromosomes without linkage disequilibrium (LD) and with a low probability of randomly similar effects.…”
mentioning
confidence: 99%
“…Genetic studies have the potential to identify molecular mechanisms of MDD vulnerability (53), but even mega-and meta-analyses of large genome-wide association studies (GWAS) have not identified genetic variants associated with MDD that survive genome-wide statistical correction (54,55). Nominally significant associations will include many false-positives.…”
mentioning
confidence: 99%
“…With recent advances in technology that enhance accessibility to genetic sequencing and analysis, studies have taken off in multiple directions to investigate implications of genetics and other biomarkers in relation to personalized assessment and treatment of depression. Although a recent genome-wide association (GWA) study of 2431 MDD patients and 3673 controls failed to identify a single genetic mechanism or pattern that predicts MDD diagnosis [10], research has begun to examine the relationships between genes and treatment efficacy, indicating possibilities for personalized care. Table 1 provides a summary of recently identified candidate genes and their proposed functional roles.…”
Section: Biological Factors: Genetics Biomarkers and Medicationsmentioning
confidence: 99%